ISSUES OF INTERPRETATION OF THE EARLY MEDIEVAL COMPLEX OF ENGINEERING STRUCTURES ON THE RUBAS RIVER (EASTERN CAUCASUS): A FORTIFICATION OR HYDRAULIC STRUCTURE? - Gmyra, Ludmila Borisovna (History, Archeology and Ethnography of the Caucasus, 2023)
The article presents new data on the functional purpose of a complex of engineering structures from the Early Middle Ages discovered in the valley of the river Rubas, located 20 km south of the city of Derbent. Excavations revealed six separate architectural objects interconnected by structural links. These objects were erected using large, finely crafted stone blocks and featured unique designs employing various construction techniques. Our initial interpretation of these engineering structures identified them as a military-technical facility with a defensive orientation. Chronologically, it was dated to the mid-6th century, considering the resemblance in construction technology to the Sasanian defensive complex in Derbent. However, additional data were uncovered, suggesting an alternative functional purpose – specifically, a hydraulic structure. Based on written sources, the construction date has been established (790-797), and the object’s purpose has been determined. The purpose of this article is to substantiate the new chronology of the discovered object and its functional orientation based on the materials from excavations of this site, incorporating information from written sources. The methodology for establishing a new chronology and functional orientation of the complex of architectural structures situated in the lower reaches of the river Rubas comprises 10 positions. These include an analysis of the design features of several structures, the presence of natural indicators, dating of the object according to written sources, and the identification of remains of structures in the riverbed of Rubas. The distinctive nature of Structure No. 5, in the form of a platform, is also highlighted. Special emphasis is placed on the historical chronicle “Derbent-name,” drawing from the writings of Arab authors from the Early Middle Ages.